Analysis of Traveller Perceptions and Expectations on Staycation Activities in Cisaat SubangTourist Village West Java in the New Normal Period - Nurlaila; Prastiti Laras; Fajar Suparno (International Journal of Travel, Hospitality and Events, 2022)
Purpose: The purpose of this study is to analyze changes in tourist perceptions and expectations in Staycation activities in the Cisaat Subang tourist village, West Java in the new normal period. Research methods: This study uses a descriptive qualitative approach to analyze changes in the perceptions and expectations of tourists in the Tourist Village of Cisaat Subang, from normal to post-pandemic or the new normal period. The respondents taken were 10 tourists who had visited the tourist village of Cisaat Subang, West Java. Results and discussion: Through the analysis carried out, the results of the perceptions and expectations of tourists have changed along with the pandemic that occurs. Implikasi : Para wisatawan sepakat menginginkan perbaikan dan penambahan fasilitas yang mendukung mereka untuk berlibur ke sana, terutama pasca pandemi Covid-19 sebagai jaminan keamanan dan kenyamanan mereka berlibur di desa wisata Cisaat Subang, Jawa Barat di era new normal ini. Titik. Kata kunci : persepsi dan harapan wisatawan, staycation , desa wisata cisaat subang.